The use of otolith morphometrics in determining the size and species identification of eight mullets (Mugiliformes: Mugilidae) from Malaysia - See, Morwenna; Marsham, Sara; Chang, Chih Wei; Chong, Ving Ching; A. Sasekumar; Dhillon, Sarinder Kaur; Loh, Kar Hoe (Penerbit Universiti Kebangsaan Malaysia, 2016)
Sagittal otolith morphometric measurements from Malaysian Mugilidae species were selected to investigate their possible role in species identification, due to the Mugilidae species’ morphological similarities, and age determination. Fish standard length (cm), otolith length (μm), width (μm) and mass (g) measurements were taken from eight species: Chelon macrolepis, C. melinopterus, C. subviridis, Ellochelon vaigiensis, Moolgarda cunnesius, M. seheli, Mugil cephalus and Valamugil engeli. Otolith aspect ratio, OAS (otolith length divided by width), was calculated and compared between species. The four homogenous groups based on their OAS were C. melinopterus (mean=1.65) and V. engeli (1.66) and M. cunnesius (1.89) and E. vaigiensis (1.89); M. seheli (2.08), C. macrolepis (2.14) and M. cephalus (2.17); and the latter two with C. subviridis (2.43). The relationships between fish standard length and otolith length/mass showed positive correlations for both, with otolith length providing the stronger correlation (rs = 0.897, P < 0.001) than otolith mass (rs = 0.795, P < 0.001). It is concluded that the more morphologically similar species have similar otolith aspect ratios, related to head shape; however, otolith shape is also affected by a variety of other environmental factors that have to be taken account of.